PERTUMBUHAN POPULASI Daphnia sp. DENGAN PEMBERIAN LARUTAN KULIT SINGKONG TERFERMENTASI - suprimantoro .; Dade Jubaedah; muslim . (Universitas Sriwijaya, 2016)
ABSTRACT Fermented cassava peels is one of the potential nutrient for growth of Daphnia sp population. This research aim was to know the influence of fermented cassava peels with yeast as source nutrition food to population growth of Daphnia sp.. This research was conducted in May 2016 Laboratory of Aquaculture, Aquaculture Program Study Sriwijaya University. This study used a complete randomized design (CRD) with four treatments and three replications i.e Daphnia sp. fed with fermented cassava peels of 0.05, 0.10, 0.15 and 0.2 g.mL-1. The data collected is a test of proximate peels before and after fermented cassava, population densities of Daphnia sp., the growth rate of population Daphnia sp., time achievement of Daphnia sp. population peak and physical chemistry of water. Research results show that fermentation by yeast can improve the nutritional value of cassava peels as a protein in by 0,45 and lower carbohidrate of 6,79, ash contentÂ 1,31, 1,04 fat and HCN 3Â Provision of fermented cassava peel solution of 0.20 g.mL-1 produces a peak population of 494 ind.L-1 to 7.3 days and the rate of population growth as much as 43.91% .days-1. Physical chemistry of water during the study are in the optimum range for growth of Daphnia sp. Keywords : Daphnia sp., cassava peels, fermentated, yeast